Physicians' perceptions of asymptomatic hyperuricemia in patients with chronic kidney disease: A questionnaire survey - Ran-hui Cha; Su Hyun Kim; Eun Hui Bae; Mina Yu; Beom Soon Choi; Hoon Young Choi; Sun Woo Kang; Jungho Shin; Sang Youb Han; Chul Woo Yang; Duk-Hee Kang (The Korean Society of Nephrology, 2019)
Background : Hyperuricemia is associated with the development and progression of chronic kidney disease (CKD) as well as cardiovascular diseases. However, there is no consistent recommendation regarding the treatment of asymptomatic hyperuricemia (AHU) in CKD patients. Here, we surveyed Korean physicians' perceptions regarding the diagnosis and management of AHU in CKD patients. Methods : Questionnaires on the management of AHU in CKD patients were emailed to regular members registered with the Korean Society of Nephrology. Results : A total of 158 members answered the questionnaire. Among the respondents, 49.4%/41.1% were considered hyperuricemic in male CKD patients whereas 36.7%/20.9% were considered hyperuricemic in female CKD patients when defined by serum uric acid level over 7.0/8.0 mg/dL, respectively. A total of 80.4% reported treating AHU in CKD patients. The most important reasons to treat AHU in CKD patients were renal function preservation followed by cerebro-cardiac protection. Majority of respondents (59.5%) thought that uric acid-lowering agents (ULAs) were the most effective method for controlling serum uric acid levels. Approximately 80% chose febuxostat as the preferred medication. A total of 32.3% and 31.0%, respectively, initiated ULA treatment if the serum uric acid level was more than 8.0 or 9.0 mg/dL, respectively. In addition, 39.2% and 30.4% answered that target serum uric acid levels of less than 6.0 or 7.0 mg/dL, respectively, were appropriate. The two major hurdles to prescribing ULAs were concerns of adverse reactions and the existing lack of evidence (i.e., the absence of Korean guidelines). Conclusion : Most Korean physicians treat AHU in CKD patients to prevent CKD progression and cerebro-cardiovascular complications.